Comparison of the Reproducibility of Various Tooth Color Measurement Techniques - Rohaninasab, Marzieh; Bahrami Maleki, Hamed; Dabiri Shahabi, Nastaran; Ahmady, Sadra (Journal of Dental School, 2025)
Objective(s): Accurate shade selection is the most challenging step in the natural reconstruction of teeth in most cases. The most commonly used method for adapting the color of tooth and restorative materials is the visual matching of the tooth color to shade guides. However, many factors affect color perception by the observer, making the visual evaluation of tooth color unreliable. Therefore, this study aimed to compare the reproducibility of tooth shade determination with two different types of spectrophotometers and two smartphone applications. Methods: The present in vitro study used four methods of colorimetry on 27 disk-shaped composite resin samples prepared from nine different shades of composite resin. Colorimetry tools included Easyshade (Vita, Germany) and SP60 (X-rite, USA) colorimetry devices, and two smartphone colorimetry applications: Color Grab and Dental Shade Navigator. Statistical analysis was performed using intraclass correlation coefficient (ICC) and repeated measures ANOVA at p<0.05. Results: The results indicated significant differences(P-value<0.05) among the four colorimetry methods, with the following reproducibility rates based on the ΔE parameter: SP60 spectrophotometer: 100%; Color Grab Software: 95.1%; Easyshade spectrophotometer: 40.7%; and Dental Shade Navigator Software: 34.4%. Conclusion: The SP60 spectrophotometer had the highest reproducibility in all the color parameters, followed by the Color Grab application. Easyshade device had a higher reproducibility rate than the Dental Shade Navigator Software.